PENGARUH UKURAN KAP, UMUR PERUSAHAAN, OPINI AUDIT DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020 - Keumala Hayati; Nadus Sofyan Sipayung; Junaedi Sihotang; Yohana Pebrina Simanjuntak (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study intends to find out the relationship between head size, companyage, audit opinion and company size on audit delay in manufacturingcompanies listed on the Indonesia Stock Exchange in 2018-2020. Theresearch method used is associative research method with quantitativeapproach. The research population is 115 companies. The samplingtechnique used is purposive sampling technique. Based on the results of theresearch, it is confirmed that partially the size of the hood has a significanteffect while Company Age, Audit Opinion, and Company Size do not have asignificant impact on audit delay for manufacturing companies listed on theIDX. However, simultaneously the size of the hood, age of the company, auditopinion and size of the company have a significant effect on audit delay formanufacturing companies listed on the BEI